2011
DOI: 10.2519/jospt.2011.0423
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neck Stress Fracture and Femoroacetabular Impingement

Abstract: The patient was a 34-year-old male recreational marathon runner referred to a physical therapist with a chief complaint of worsening right lateral hip pain of 3 months duration that was insidious in nature. Following a physical examination, the physical therapist discussed his suspicions with the referring physician. Magnetic resonance imaging revealed findings consistent with a stress fracture at the inferomedial right femoral neck, a mild cam-type deformity of the right femoral neck, and a mild degree of het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…11 Based on this, the authors concluded that impingement should be addressed at the same time as the fracture fixation. In this context, a correlation between FAI and femoral neck stress fractures has also been described, 12 where the Pincer morphology was found to be associated with 78% of femoral neck fracture. 13 It is also known that the femoroacetabular impingement is associated with posterior hip dislocation.…”
Section: Introductionmentioning
confidence: 91%
“…11 Based on this, the authors concluded that impingement should be addressed at the same time as the fracture fixation. In this context, a correlation between FAI and femoral neck stress fractures has also been described, 12 where the Pincer morphology was found to be associated with 78% of femoral neck fracture. 13 It is also known that the femoroacetabular impingement is associated with posterior hip dislocation.…”
Section: Introductionmentioning
confidence: 91%
“…Further factors found to pre-dispose individuals to develop FNSFs include a sudden increase in training intensity, coxa vara, coxa profunda and acetabular retroversion, as seen in pincer-type femoral acetabular impingement (FAI) 14 25 39 . However, an established link between FNSF and FAI has yet to be confirmed 25 34 59 .…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…The return-to-sport data in the current literature for athletes with FNSFs is limited, with only 2 studies and one systematic review providing comprehensive information on return to sport for these injuries ( Table 2 ) 30 49 . The remaining literature is restricted to case reports and case series ( Table 3 ) 5 6 7 11 13 15 16 18 20 26 27 28 32 33 36 38 41 43 46 51 55 57 58 59 61 62 63 .…”
Section: Return To Sport and Injury Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…If osteoarthritis was previously developed by FAI before stress fracture, hip symptoms can persist after fracture healing. When the stress fracture is associated with FAI, the combined cam or pincer lesion can be corrected with internal fixation by debridement of protruded head-neck junction and superior labrum [10]. We performed total hip arthroplasty because of combined hip osteoarthritis and the avoidance of nonunion by repeated abuttment.…”
Section: Discussionmentioning
confidence: 99%